2007
DOI: 10.1002/pen.20886
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the balance between impact strength and stiffness in polypropylene/elastomer blends by incorporation of a nucleating agent

Abstract: Isotactic polypropylene (iPP) blends were prepared with two different thermoplastic elastomers, a triblock copolymer styrene–ethylene butylene–styrene (SEBS) and a metallocenic ethylene‐octene copolymer (EO). The mechanical properties and morphology of blends with 0–50 wt% elastomer were studied to determine the influence of the presence of the elastomer on the improvement of toughness. The addition of a nucleating agent as a third component exerted a significant effect on the overall properties. Dynamic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 51 publications
2
38
1
Order By: Relevance
“…In the other hand, it can observe that SEBS presence causes a slight decrease in melting temperature when SEBS amount increase in blends, being more significant for linear than radial SEBS, indicative that PP crystalline phase is changing due the presence of processing oil added. There are reports that SBS and SEBS have a nucleating effect in blends with isotactic PP and nylon 6, which it is not observed in present work [7] . …”
Section: Differential Scanning Calorimetry (Dsc)contrasting
confidence: 50%
See 1 more Smart Citation
“…In the other hand, it can observe that SEBS presence causes a slight decrease in melting temperature when SEBS amount increase in blends, being more significant for linear than radial SEBS, indicative that PP crystalline phase is changing due the presence of processing oil added. There are reports that SBS and SEBS have a nucleating effect in blends with isotactic PP and nylon 6, which it is not observed in present work [7] . …”
Section: Differential Scanning Calorimetry (Dsc)contrasting
confidence: 50%
“…The addition of a nucleant agent has been studied to improve the mechanical properties in a PP/SEBS proportion close to 50% [7] . An important issue in SEBS-PP blends is the processing conditions (temperature profile, screw and feeding speed), due to mechanical properties on phase dispersion can vary according to the conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The respective influence of nucleating agents (α or β) on the mechanical performances of heterophasic systems composed of an iPP matrix and an ethylene-propylene rubber (EPR) is still controversial, consequence of a lack of published experimental data. Whereas several studies have reported positive effects of nucleation on the fracture resistance of iPP/EPR blends [6][7][8][9][10][11][12], other contributions showed limited (for β-nucleation) [4,[13][14][15][16] or even negative (for α-nucleating agents) ones [4,17,18]. The goal of the present investigation was to identify potential coupling effect between the matrix crystalline structure induced by nucleation and the morphology of the rubbery phase in order to clarify this apparent contradiction.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, however, polymer structure plays a decisive role for the actual effects. Toughness increase by α-nucleation has been demonstrated for high-flow PP homopolymers 10 , for blends with external elastomers 24 and for heterophasic ethylenepropylene copolymers with specific elastomer design 25 . No such data, which reports the enhancement of impact resistance by specific nucleation, have been shown for random copolymers so far.…”
Section: Introductionmentioning
confidence: 99%